Gothic architecture from 'La France pittoresque. Ouvrage illustré, etc'. - Auteur inconnu... (The British Library, 1893)
Notice issue d Europeana. This image has been taken from scan 000358 from "La France pittoresque. Ouvrage illustre, etc". The title and subject terms of this image have been generated from tags, created by users of the British Library's flickr photostream.
http://creativecommons.org/publicdomain/mark/1.0/
Keywords: europeana; image; patrimoine europeen; Bibliothèque numerique; iconographie